Do Funerals Funds by Informal Institution Comply with Microtakaful Principles? - Firdaus, Achmad; Dewi, Erwita Triana; Komalasari, Ratna (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2021)
Research on funeral funds on a homeowner association has never been performed before. Meanwhile, previous studies on the funeral fund in insurance companies, 'rukun kematian,' and mosques are used as a reference. The research aims to analyze whether the funeral funds managed by informal institutions correspond with the micro takaful principle. Method is a descriptive analysis is used by comparing the survey in two groups, namely residential and village areas, of 31 communities spread across Java Island. The research variables developed include calculation, collection method, and amount of funeral fund contribution, alongside the calculation and amount of benefits. Although the funeral funds' variables have not fulfilled the micro takaful principle, there are interesting findings. These include that the calculation of contribution for the two groups, namely the residential and village areas, is performed by mutual agreement through community deliberations. In the village, the collection method is by direct payment from members of the public to the officers, which is different from the residential areas, where it is picked up by the officers. Furthermore, the amount of funding contributions to the community in the villages is around Rp. 3.001 and Rp. 5,000, while the total is over Rp. 10,000 in residential areas. The informal funeral funding scheme (IFFS) has become a mutually beneficial culture of Indonesian society, which fosters strong humanity and brotherhood. This scheme can be formulated in micro-takaful cooperatives to ensure that the benefits trickle down for every member of the community, including Muslims and non-Muslims.